THE ESTABLISHMENT OF PANCASILA AS THE GROUNDING PRINCIPLES OF INDONESIA - Megawati Soekarnoputri (The Republic of Indonesia Defense University, 2021)
Grounding Pancasila is the driving force and energy to make Pancasila in the concept of political, economic, social, cultural, as well as mental and spiritual development. The study aims to analyze the power of Pancasila as a basic assumption of Indonesian to respond to recent challenges faced by this country. This study employs a deconstruction approach that aims to describe how Pancasila become Indonesia's Basic Principles. The historical methods are heuristics, verification, interpretation, and historiography. Sources of data obtained are reading Soekarno's thoughts through his work